Determination of total microorganisms count and vibrio species profile in freshwater fish - Azmi, Nor Aqilah Mohamed (Universiti Sains Malaysia, 2017)
Fish consist of freshwater fish and marine fish are known as one of the main protein sources in human diet. Freshwater fish have a great taste, rich with nutritive values and many other health benefits. However, freshwater fish appealed to be a potential vector of Vibrio microorganisms such as V. cholerae, V. parahaemolyticus and V. vulnificus. Yet, very little information about the microorganisms risk assessments especially Vibrio in freshwater fish as there is no standard of permissible for Vibrio microorganisms in Malaysia. In this project, a study was conducted in order to assess the microorganisms risk and presence of Vibrio in freshwater fish. Different species of freshwater fish (n=10) were obtained from wet markets within Kota Bharu, Kelantan. The total microorganisms count was determined using spread plate method and Vibrio profile used Thiosulfate Citrate Bile Salts Sucrose (TCBS) agar, Tryptone Salt (T1N1) agar for purity and salt tolerance test for Vibrio spp. confirmation test. The results had shown that ‘Tilapia Hitam’ (Oreochromis mossambicus') had the highest total microorganisms count at 3.34 106 cfu/g as compared to the other freshwater fish samples. The limit for total microorganisms count in fishery products of Malaysia is at 106 per gram, and 80% of the freshwater fish samples in this study were within the permissible limit set by Ministry of Health Malaysia. For the Vibrio microorganisms profile, 20% of freshwater fish samples detected with both V. cholerae and V. parahaemolyticus, while 80% from the freshwater fish samples had only V. cholerae. In conclusion, it was suggested that Vibrio can be found in freshwater fish. Thus, proper handling of freshwater fish must be practiced in order to decrease the incidence of foodbome illness due to these microorganisms. Further research should be done to enhance the food safety of freshwater fish consumption, hence able to set the standard of permissible for Vibrio microorganisms in Malaysia.